Pemanfaatan Google Drive Untuk Pengarsipan Data Digital Bagi SDM PKH Kabupaten Garut - Setiawan, Topan; Yudha, Mohamad Fandra Yudha (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2021)
In the current technological era, data archiving is not only done manually in physical form but also in digital form which is stored in cloud storage. Archiving data for PKH workers in Garut Regency is important as a form of administrative activity, so that all types of information received can be managed and implemented properly. Digital data archiving through cloud storage such as Google Drive will provide convenience for PKH workers in data management and information exchange. In fact, currently most workers do not know the benefits of Google Drive. Even though Google Drive is free, the utilization of Google Drive among PKH workers is still low. Therefore, this training is expected to provide deeper knowledge about the use of Google Drive so that it can support administrative activities more optimally.